2020
DOI: 10.3389/fvets.2020.569370
|View full text |Cite
|
Sign up to set email alerts
|

Actinobacillus pleuropneumoniae Interaction With Swine Endothelial Cells

Abstract: Actinobacillus pleuropneumonia is a swine (host) specific respiratory pathogen and the etiological agent of swine pleuropneumonia which affects pigs of all ages, many being asymptomatic carriers. This pathogen has high morbidity and mortality rates which generates large economic losses for the pig industry. Actinobacillus pleuropneumoniae is a widely studied bacterium, however its pathogenesis is not yet fully understood. The prevalence of the 18 serotypes of A. pleuropneumoniae varies by geographic region, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…25,26 It may induce cell apoptosis during expression, thereby impacting the normal expression of the chimeric protein. Additionally, App1766, falling within the range of 200−300 aa, displayed partial solubility (Figure 2B), which might be influenced by its unique physicochemical properties as an outer membrane protein of Klebsiella pneumoniae, potentially adsorbing onto E. coli and inducing cell lysis, 27 thereby allowing partial expression in the supernatant. Moreover, despite forming inclusion bodies, the expression levels of dMS2-GST and dMS2-eGFP revealed relatively higher levels.…”
Section: ■ Discussionmentioning
confidence: 99%
“…25,26 It may induce cell apoptosis during expression, thereby impacting the normal expression of the chimeric protein. Additionally, App1766, falling within the range of 200−300 aa, displayed partial solubility (Figure 2B), which might be influenced by its unique physicochemical properties as an outer membrane protein of Klebsiella pneumoniae, potentially adsorbing onto E. coli and inducing cell lysis, 27 thereby allowing partial expression in the supernatant. Moreover, despite forming inclusion bodies, the expression levels of dMS2-GST and dMS2-eGFP revealed relatively higher levels.…”
Section: ■ Discussionmentioning
confidence: 99%
“…23 Other microbiomes were also regulated in mild and severe disease, such as Actinobacillus. Actinobacillus is a type of opportunistic pathogen resident in the human lung, and an altered proportion of them may cause the genesis of disease such as infectious pneumonia; [24][25][26] Aggregatibacter is thought to be a common pathogen and has been found to be a cause of human pneumonia. 27 Besides, Deinococcus is a type of bacteria colonized in dirt and the host gut, and limited searches found that it participated in respiratory disease.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, AasP is also related to other proteins of the SPATE family of serine proteases. Plasencia-Muñoz et al ( 115 ) identified in immunoblot a band with a molecular weight of 100 kDa using a polyclonal antibody against Vat toxins, weight like the AasP protein. In a cellular interaction, the internalization of the bacteria is observed as the formation of vacuoles in endothelial cells in an in vitro cell model.…”
Section: Cell Integritymentioning
confidence: 99%